Advanced Biomanufacturing Technologies for Micro-physiological Systems - Kim, Min Kyeong; Yoon, Jungbin; Kim, Dohui; Kim, Jongmin; Kim, Jae-Seok; Go, Gyugang; Song, Junhyeok; Son, Seunghun; Park, Kyungdeok; Lee, Jooyoung; Lee, Donghan; Cho, Sumin; et al. (한국정밀공학회, 2025)
Advanced biomanufacturing technologies are rapidly transforming the development of microphysiological systems (MPS), which serve as sophisticated in vitro platforms to model human organ structure and function with high fidelity. This review highlights cutting-edge biofabrication strategies, including 3D bioprinting technologies (such as inkjet, extrusion-based, digital light processing, stereolithography, and laser direct writing), microfluidics, modular tissue engineering, and electrohydrodynamic manufacturing that enable precise fabrication of complex, multicellular, and physiologically relevant tissue models. The integration of microfluidic systems enhances MPS by supporting dynamic perfusion, mechanical stimulation, and real-time monitoring, while modular approaches such as cell spheroid, organoid, and cell sheet assembly facilitate scalable and reproducible tissue engineering. Electrohydrodynamic techniques like electrospinning and melt electrowriting are emphasized for their ability to fabricate nanostructured scaffolds that closely mimic native extracellular matrix properties. This review also examines the selection and application of biomaterials, ranging from natural and synthetic polymers to hybrid composites and stimuli responsive hydrogels, that underpin the structural and functional integrity of MPS. Finally, the broad applications of advanced biomanufactured MPS in drug screening, toxicology, disease modeling, and regenerative medicine are discussed, emphasizing their potential to reduce reliance on animal models and accelerate biomedical discoveries toward clinical translation. The convergence of real-time sensing, smart materials, and modular design principles is identified as a key driver for the next generation of physiologically relevant and patient specific in vitro models.